A systematic review and meta-analysis on the efficacy of antibiotic treatment in controlling colibacillosis in broiler production - Ronald Vougat Ngom; Helena Cardoso de Carvalho Ferreira; Gaspard Ayissi; Akenghe Tanyienow; Alessandra Piccirillo (PLoS ONE, 2025)
The aim of this study was to evaluate, through a systematic review and meta-analysis, the efficacy of antibiotics in controlling colibacillosis in broiler production, by synthesizing evidence from randomized controlled trials (RCTs). The Cochrane method and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed, and the databases CAB abstract, Agricola, PubMed and Web of Science were searched using relevant keywords to identify studies. Eligible studies had to report at least one of the following outcomes: mortality, feed conversion ratio (FCR), condemnations at slaughter and total antibiotic use. Risk of bias (RoB) by outcome of individual study and pairwise meta-analysis by outcome and antibiotic or antibiotics combination, when at least three studies were available, were also conducted. Out of 24,778 articles found in the searched databases, 48 studies were eventually selected. Most of the studies reported mortality as outcome (n = 43) and tested the antibiotic as metaphylactic treatment (n = 41). A total of 47 antibiotics belonging to 18 different classes were tested in the selected studies with enrofloxacin as the most studied. The overall RoB was “some concerns” in 78.2% of studies for mortality outcome and 73.7% for FCR outcome. Meta-analysis showed that doxycycline (0.04; 95% CI 0.02-0.10; P < 0.001) had the highest protective effect against mortality due to colibacillosis, followed by spectinomycin (0.11; 95% CI 0.05-0.26; P < 0.001), enrofloxacin (0.12; 95% CI 0.06-0.25; P < 0.001), lincomycin plus spectinomycin (0.22; 95% CI 0.13-0.38; P < 0.001), flumequine (0.25; 95% CI 0.14-0.44; P < 0.001) and oxytetracycline (0.31; 95% CI 0.20-0.50; P < 0.001). However, these results should be interpreted with caution due to the low number of studies included in the meta-analysis and the high variability in the animal models and study designs across RCTs. This review underscores the necessity for continued research to refine treatment strategies of colibacillosis in broiler production in line with the evolving regulatory and public health guidelines related to antibiotic use in animals.